-3n+18=-6(n+1)

Simple and best practice solution for -3n+18=-6(n+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3n+18=-6(n+1) equation:


Simplifying
-3n + 18 = -6(n + 1)

Reorder the terms:
18 + -3n = -6(n + 1)

Reorder the terms:
18 + -3n = -6(1 + n)
18 + -3n = (1 * -6 + n * -6)
18 + -3n = (-6 + -6n)

Solving
18 + -3n = -6 + -6n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '6n' to each side of the equation.
18 + -3n + 6n = -6 + -6n + 6n

Combine like terms: -3n + 6n = 3n
18 + 3n = -6 + -6n + 6n

Combine like terms: -6n + 6n = 0
18 + 3n = -6 + 0
18 + 3n = -6

Add '-18' to each side of the equation.
18 + -18 + 3n = -6 + -18

Combine like terms: 18 + -18 = 0
0 + 3n = -6 + -18
3n = -6 + -18

Combine like terms: -6 + -18 = -24
3n = -24

Divide each side by '3'.
n = -8

Simplifying
n = -8

See similar equations:

| 12x-34=46+7x | | 12b=.2 | | (6g-9)+1/3(15-9g)= | | 12+3d=d | | 5.7+b=23 | | -4x+82=-86-10x | | 25=n-(3) | | R^2=-96 | | (0.01)(1)+0x=0.02(x+1) | | 24x^2-58x+40=7 | | 2/3y-12 | | 17=-d | | -2=j-3/2 | | 3.2+9.3x=0.2x+1.4 | | -5+6f=5f+2 | | 3/2(5x-4)+1=1/3x-2(x-5) | | -8(x+2)=-3x-31 | | -1/2-7=_ | | 2/8k=16/24 | | 6y-10+6y+10= | | -6g+8=-4g | | 5x-8=6x+15 | | -5t^2-8t=-120 | | -3b+4b=14-b | | 10x+-5=3x+9 | | 13=-3n+11-n | | 1/12x=3 | | 7(5x+3)=371 | | 72=-8u | | 1/2(8x-6)=9 | | 6(5x+7)=102 | | -13=y/2 |

Equations solver categories